Malignant glomus tumor of the breast: a case report - Mou, Qian; Jiang, Zhenpeng; Zhou, Jiaojiao (Frontiers in Oncology, 2024)
Malignant glomus tumor (MGT) is a rare mesenchymal neoplasm. It is rarely located in the breast. We present a case of a 57-year-old female, presenting with complaints of a progressively growing mass found in her left breast. Though multiple imaging examinations have been performed, especially multimodal ultrasound examinations, an accurate diagnosis still cannot be determined. Finally, the lesion was confirmed to be a MGT of the breast by postoperative pathological diagnosis. In conclusion, MGT originating from breast is extremely rare. No case has never been described before. This study demonstrates the imaging characteristics of a patient with MGT of the breast, in order to provide more extensive insights to consider the differential diagnosis of breast lesions.